One Size Fits (n)One: The Influence of Sex, Age, and Sexual Human Immunodeficiency Virus (HIV) Acquisition Risk on Racial/Ethnic Disparities in the HIV Care Continuum in the United States. (31st August 2018) - Desir, Fidel A; Lesko, Catherine R; Moore, Richard D; Horberg, Michael A; Wong, Cherise; Crane, Heidi M; Silverberg, Michael; Thorne, Jennifer E; Rachlis, Beth; Rabkin, Charles; Mayor, Angel M; Mathews, William C; et al.
Abstract: Background: The United States National HIV/AIDS Strategy established goals to reduce disparities in retention in human immunodeficiency virus (HIV) care, antiretroviral therapy (ART) use, and viral suppression. The impact of sex, age, and sexual HIV acquisition risk (ie, heterosexual vs same-sex contact) on the magnitude of HIV-related racial/ethnic disparities is not well understood. Methods: We estimated age-stratified racial/ethnic differences in the 5-year restricted mean percentage of person-time spent in care, on ART, and virally suppressed among 19 521 women (21.4%), men who have sex with men (MSM; 59.0%), and men who have sex with women (MSW; 19.6%) entering HIV care in the North American AIDS Cohort Collaboration on Research and Design between 2004 and 2014. Results: Among women aged 18–29 years, whites spent 12.0% (95% confidence interval [CI], 1.1%–20.2%), 9.2% (95% CI, .4%–20.4%), and 13.5% (95% CI, 2.7%–22.5%) less person-time in care, on ART, and virally suppressed, respectively, than Hispanics. Black MSM aged ≥50 years spent 6.3% (95% CI, 1.3%–11.7%), 11.0% (95% CI, 4.6%–18.1%), and 9.7% (95% CI, 3.6%–16.8%) less person-time in these stages, respectively, than white MSM ≥50 years of age. Among MSM aged 40–49 years, blacks spent 9.8% (95% CI, 2.4%–16.5%) and 11.9% (95% CI, 3.8%–19.3%) less person-time on ART and virally suppressed, respectively, than whites. Conclusions: Racial/ethnic differences in HIV care persist in specific populations defined by sex, age, and sexual HIV acquisition risk. Clinical and public health interventions that jointly target these demographic factors are needed. Abstract : Older black men who have sex with men, young white women, and middle-aged black men who have sex with women represent new key targets for future clinical and public health initiatives to reduce racial/ethnic differences in Human Immunodeficiency Virus care.